Effects of the controlled-released TGF-beta 1 from chitosan microspheres on chondrocytes cultured in a collagen/chitosan/glycosaminoglycan scaffold - Lee, JE; Kim, KE; Kwon, IC; Ahn, HJ; Lee, SH; Cho, HC; Kim, HJ; Seong, SC; Lee, MC (ELSEVIER SCI LTD, 2004)
The objectives of this study were (1) to develop a three-dimensional collagen/chitosan/glycosaminoglycan (GAG) scaffold in combination with transforming growth factor-beta1 (TGF-beta1)-loaded chitosan microspheres, and (2) to evaluate the effect of released TGF-beta1 on the chondrogenic potential of rabbit chondrocytes in such scaffolds. TGF-beta1 was loaded into chitosan microspheres using an emulsion-crosslinking method. The controlled release of TGF-beta1, as measured by enzyme-linked immunosorbent assay (ELISA), was monitored for 7 days. The porous scaffolds containing collagen and chitosan were fabricated by using a freeze drying technique and crosslinked using 1-ethyl-3-(3-dimethyl aminopropyl)carbodiimide (EDC) in the presence of chondroitin sulfate (CS), as a GAG component. The TGF-beta1 microspheres were encapsulated into the scaffold at a concentration of 10 ng TGF-beta1/scaffold and then chondrocytes were seeded in the scaffold and incubated in vitro for 3 weeks. Both proliferation rate and glycosaminoglycan (GAG) production were significantly higher in the TGF-beta1 microsphere-incorporated scaffolds than in the control scaffolds without microspheres. Extracellular matrix staining by Safranin O and imimmohistochemistry for type II collagen were elevated in the scaffold with TGF-beta1 microspheres. These results suggest that TGF-beta1 microspheres when incorporated into a scaffold have the potential to enhance cartilage formation. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: GROWTH-FACTOR BETA-1; ARTICULAR-CARTILAGE; ENZYMATIC DEGRADATION; COLLAGENOUS MATRICES; GENE DELIVERY; CROSS-LINKING; TISSUE; GLYCOSAMINOGLYCANS; HYDROGEL; DNA